238 Effects of algae DHA on parameters of nutrient digestibility, blood coagulation and serum fatty acid profile. (5th December 2019) - James, Carrie; He, Fei; Mangian, Heather; Hoke, Jolene; Davenport, Gary; de Godoy, Maria R C
Abstract: Algae can be a sustainable alternative for dietary supplementation of omega-3 polyunsaturated fatty acids (w3-PUFAs; DHA and EPA), however there is limited information on the safety and bioavailability of w3-PUFAs from algal sources in feline diets. Thus, the objective of this study was to determine the effects of dietary supplementation of Algal-DHA on plasma fatty acid profile, blood coagulation, and apparent total tract nutrient digestibility (ATTD) in adult cats. Three diets were formulated to contain poultry fat or a 2% inclusion of fish oil or DHA-algal meal. Thirty female and male adult cats (mean age: 1.8 ± 0.03 yrs, mean BW: 4.5 ± 0.8 kg) were used in a complete randomized design and fed assigned diets for 90 days. Fasted blood samples were collected on days 0, 30, 60 and 90 and analyzed for serum chemistry, complete blood count, coagulation factors, and plasma fatty acid profile. At the end of the experimental period, a 4-d total fecal collection was performed for determination of ATTD of macronutrients and fecal score. There were no significant (P > 0.05) differences in food intake, fecal output and scores among dietary treatments. Similarly, ATTD of dry matter and organic did not differ (P > 0.05) among diets. Dietary supplementation of fish oil or algal-DHA did not affect (P > 0.05) plasma prothrombin time or partial thromboplastin time. All cats remained healthy throughout the study. Serum triglyceride concentrations were within reference range, but were significantly higher for DHA on days 30 and 90 vs. day 0. Results gathered herein indicate that feeding an algal-DHA enriched diet is safe and will not negatively impact nutrient digestibility, food intake, or coagulation factors in adult cats.